The international WAO/EAACI guideline for the management of hereditary angioedema—The 2017 revision and update - Maurer, M.; Magerl, M.; Ansotegui, I.; Aygören‐Pürsün, E.; Betschel, S.; Bork, K.; Bowen, T.; Balle Boysen, H.; Farkas, H.; Grumach, A. S.; Hide, M.; Katelaris, C.; et al. (Allergy (Copenhagen), 2018)
Hereditary Angioedema (HAE) is a rare and disabling disease. Early diagnosis and appropriate therapy are essential. This update and revision of the global guideline for HAE provides up‐to‐date consensus recommendations for the management of HAE. In the development of this update and revision of the guideline, an international expert panel reviewed the existing evidence and developed 20 recommendations that were discussed, finalized and consented during the guideline consensus conference in June 2016 in Vienna. The final version of this update and revision of the guideline incorporates the contributions of a board of expert reviewers and the endorsing societies. The goal of this guideline update and revision is to provide clinicians and their patients with guidance that will assist them in making rational decisions in the management of HAE with deficient C1‐inhibitor (type 1) and HAE with dysfunctional C1‐inhibitor (type 2). The key clinical questions covered by these recommendations are: (1) How should HAE‐1/2 be defined and classified?, (2) How should HAE‐1/2 be diagnosed?, (3) Should HAE‐1/2 patients receive prophylactic and/or on‐demand treatment and what treatment options should be used?, (4) Should HAE‐1/2 management be different for special HAE‐1/2 patient groups such as pregnant/lactating women or children?, and (5) Should HAE‐1/2 management incorporate self‐administration of therapies and patient support measures?